2003
DOI: 10.2535/ofaj.80.29
|View full text |Cite
|
Sign up to set email alerts
|

Which Portion in a Facet is Specifically Affected by Articular Cartilage Degeneration with Aging in the Human Lumbar Zygapophysial Joint?

Abstract: Summary: Using 10 osteoligamentous vertebral columns obtained from elderly donated cadavers, we describe in detail degenerative changes of the articular cartilage in lumbar zygapophysial joints to show which portion in a facet is specifically affected. Degenerative changes, including extended cartilage defects, occurred in multiple facets of every specimen. The results demonstrated 5 basic morphologies of degeneration, i.e., 1) marginal dominace in the articular surface, 2) lower segment dominance except for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…This disparity was hypothesized as the reason for increased rates of pathology found in the talar dome compared to the tibial plafond. Within the human facet literature, there is conflict with regard to disposition of pathology, since some report a higher incidence of degeneration in the inferior facet surface [44] while others have concluded that the superior facet joint surface is more susceptible to pathology [45]. The biomechanical properties of human facet cartilage were not collected in this study due to the high incidences of pathology, and it remains unclear if disparities exist across the articulating surfaces of human facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity was hypothesized as the reason for increased rates of pathology found in the talar dome compared to the tibial plafond. Within the human facet literature, there is conflict with regard to disposition of pathology, since some report a higher incidence of degeneration in the inferior facet surface [44] while others have concluded that the superior facet joint surface is more susceptible to pathology [45]. The biomechanical properties of human facet cartilage were not collected in this study due to the high incidences of pathology, and it remains unclear if disparities exist across the articulating surfaces of human facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have also reported that osteophytes form along the posterior capsular attachment where the compressive and tensile stresses can become excessive in the hypermobile degenerative joint [1,296]. Furthermore, the posterior region of the facet joint is also found to be the most frequent location of cartilage defects [297], which may mean that nonphysiologic mechanical stresses develop at this location during extension when the intervertebral disc height decreases (because of disc degeneration or disc arthroplasty), making the posterior edge of the superior facet collide with the lamina of the inferior vertebra. Furthermore, an increase in the mechanical stress experienced by the bony articular pillar can also initiate or exacerbate degeneration by overstimulation of bone cells activity.…”
Section: Facet Joint Degeneration and The Bony Pillarsmentioning
confidence: 99%
“…A degeneração da coluna é um evento muito comum. As alterações morfológicas foram descritas macroscopicamente [5][6][7] , histolologicamente 8 , e utilizando muitas técnicas de imagens diferentes tais como radiografia simples, discografia ressonância magnética ou tomografia computadorizada [9][10][11][12] . A literatura mostra diminuição da cartilagem articular, esclerose óssea subcondral, formação de osteófitos, hipertrofia e mais recentemente, degeneração facetá-ria 13 .…”
Section: Objetivos: Presentar Las Manifestaciones Clínicas Y Radiológunclassified
“…Havia 95 mulheres e 67 homens no total de pacientes. A tomografia computadorizada, radiografia simples (AP, lateral e dinâmicas) e resultados clínicos foram coletados no pré-operatório, 3,6,12,24,36,48,60, 72 e 84 meses após a cirurgia. O Índice de Incapacidade Relacionada ao Pescoço -Neck Disability Index (NDI) e a Escala Visual Analógica (EVA) foram utilizados para avaliar dor e resultados funcionais.…”
Section: Materiais E Métodosunclassified